Exclusive breastfeeding: the long distance between discourse and practice - Del Ciampo, Luiz Antonio; Del Ciampo, Ieda Regina Lopes (International Journal of Research in Medical Sciences, 2025)
The article by Hiranmayi et al recently published in this journal, allows us to revive the discussion on a topic of extreme importance for the health of both mother and child, especially when it comes to first-time mothers: exclusive breastfeeding. The study assessed the knowledge, attitudes, and practices of first-time mothers with children up to six months of age regarding infant feeding, particularly related to exclusive breastfeeding. Although 85% of participants were aware of the recommended duration of exclusive breastfeeding, only 52.2% practiced it, highlighting barriers such as the perception of insufficient milk supply, returning to work, and lack of support from family members or healthcare professionals.